THE EFFECT OF Streptococcus sp AND Lactobacillus sp ATTACHMENT ON THE LEVEL OF FLUORIDE ION SOLUBILITY IN GIC RESTORATION - Rizki Fajar Fauzan; Muhammad Yanuar Ichrom Nahzi; Buyung Maglenda (FKG Unlam, 2020)
Background: Glass ionomer cement (GIC) is a restoration material that has the ability to release Fluoride ion. The Extrinsic factor that affect the solubility of fluoride is low or acidic pH. Streptococcus sp and Lactobacillus sp are asiduric and acidogenic bacteria which are resistant to acidic conditions and may produce acid. A lower pH (acid) causes higher level of fluoride to be released. Objective: This study was to analyze the effect of Streptococcus sp and Lactobacillus sp attachment on solubility of fluoride level on GIC restoration Method: Twenty-one specimens (5mm diameter x 2mm thickness; n = 7 / group) were fabricated with GIC. The treatment group (Streptococcus sp and Lactobacillus sp) while the control group (Artificial Saliva) was immersion for 7 days in an incubator 37oC. Solubility of fluoride was measured using a pH meter Lutron (208) TL Lutron (Taiwan). Result: One Way Anova and Post Hoc Bonferonni showed that there were significant differences between the treatment groups of Streptococcus sp (5.13 ± 0.86ppm) and Lactobacillus sp (6, 02 ± 0.79ppm) with artificial Saliva group controls (3.03±0,56ppm). Conclusion: There was an effect of Streptococcus sp and Lactobacillus sp bacteria attachment on the solubility of fluoride from the GIC restoration.